Patient preferences in adjuvant and palliative treatment of advanced melanoma: A discrete choice experiment - Weilandt, Juliane; Schaarschmidt, Marthe-Lisa; Kiecker, Felix; Sasama, Bianca; Pronk, Melanie; Ohletz, Jan; Koennecke, Andreas; Mueller, Verena; Utikal, Jochen; Hillen, Uwe; Harth, Wolfgang; Peitsch, Wiebke K.; et al. (Acta Dermato-Venereologica, 2020)
Treatment paradigms for advanced melanoma have changed fundamentally over recent years. A discrete choice experiment was performed to explore patient preferences regarding outcome (overall response rate, 2-year survival rate, progression-free survival, time to response, type of adverse events, probability of adverse event-related treatment discontinuation) and process attributes (frequency and route of admi-nistration, frequency of consultations) of modern treatments for melanoma. Mean preferences of 150 patients with melanoma stage IIC–IV were highest for overall response rate (relative importance score (RIS) 26.8) and 2-year survival (RIS 21.6), followed by type of adverse events (RIS 11.7) and probability of adverse event-related treatment discontinuation (RIS 9.2). Interest in overall response rate and 2-year survival declined with increasing age, whereas process attributes gained importance. Participants who had expe-rienced treatment with immune checkpoint inhibitors valued overall response rate more highly and worried less about the type of adverse events. In conclusion, patients with advanced melanoma consider efficacy of treatment options most important, followed by safety, but preferences vary with individual and disease-rela-ted characteristics.
CRIS-Team Scopus Importer:2021-12-06
Keywords: BRAF inhibitors; Conjoint analysis; Immune checkpoint inhibi-tors; Melanoma; Patient preferences; Targeted therapy